ANALISIS PENERIMAAN PAJAK HOTEL DAN RESTORAN SEBAGAI SUMBER PENDAPATAN ASLI DAERAH KOTA MADIUN (Studi Pada Dinas Pendapatan Daerah Kota Madiun Tahun 2009-2013) - ANGGRAINI, SEPTIA DWI (Jurnal Mahasiswa Perpajakan, 2015)
Madiun city is as one of business economic growth in East Java then investment are expected to be increased for the economic growth. The development of hotel and restaurant in Madiun City is right choices because it has potential market that supported by strategic location. The hotel and restaurant tax are the type of local tax potential to be improved and be able to support local revenue of Madiun. Methods used of the research is descriptive quantitative. Variables are using contribution, effectiveness and growth rate that is an analysis of the data used to research. The research indicated the results of the average contribution of the hotel and restaurant tax during 2009-2013 years is 2,26 % and 2,84 %. The effectiveness of tax revenue hotel and restaurant tax in 2009-2013 year shows the average 113,55 % and 120,50 %. The rate of growth the hotel and restaurant tax shows the average 23,42 % and 31,27 %. The efforts which done by Dinas Pendapatan Daerah Kota Madiun to increase tax of the hotels and restaurants revenue through intensification and extensification. Keywords : Hotel Tax, Restaurant Tax, Local Tax, Local Revenue